Successful pregnancies and a live birth after intracytoplasmic sperm injection in globozoospermia - Manish R Banker; Pravin M Patel; Bharat V Joshi; Preeti B Shah; Rakhi Goyal (Wolters Kluwer Medknow Publications, 2009)
Globozoospermia is a severe form of teratozoospermia characterized by round-headed acrosomeless spermatozoa. Here we present two successful pregnancies and a live birth after intracytoplasmic sperm injection.